2009
DOI: 10.1016/j.nbt.2009.06.762
|View full text |Cite
|
Sign up to set email alerts
|

Determination of chromosomes controlling physiological traits associated to salt tolerance in barley in seedling stage

Abstract: by these QTLs varies from 7.07 to 39.04%. Highest LOD scores were obtained for the leaf to stem ratio on chromosome 2H. QTLs for forage quality indexes (total digestible nutrient, dry organic matter digestibility, leaf to stem ratio and seed to forage ratio) were found on chromosomes 1H, 2H, 3H and 5H. QTLs for forage quantity indexes (forage wet and dry matter) were mapped on chromosomes 1H, 2H, 3H and 5H. Mapped QTLs appear to be stable between locations. Therefore, gain through marker-assisted selection (MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Various fluorescence parameters have been found to be closely correlated with carbon assimilation under different stresses in rice (Guo et al 2008), lucerne (Smethurst and Shabala 2003), soybean (Yin et al 2010), wheat ) and maize (Fracheboud et al 2004), as well as grain yield in barley (Bertholdsson 2013) and, under optimal conditions intriticale (Hura et al 2009). Fluorescence parameters has also been used for mapping QTL in relation to drought stress in wheat (Czyczyło-Mysza et al 2011), rice (Gu et al 2012) and barley (Guo et al 2008;Wójcik-Jagla et al 2013), salt tolerance in barley (Aminfar et al 2011) and biomass and yield in wheat (Czyczylo-Mysza et al 2013). However, to our knowledge there have been no previous efforts to associate chlorophyll fluorescence with WLT, besides research by Pang et al (2004) and Bertholdsson (2013), who used it to characterise WLT of barley cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…Various fluorescence parameters have been found to be closely correlated with carbon assimilation under different stresses in rice (Guo et al 2008), lucerne (Smethurst and Shabala 2003), soybean (Yin et al 2010), wheat ) and maize (Fracheboud et al 2004), as well as grain yield in barley (Bertholdsson 2013) and, under optimal conditions intriticale (Hura et al 2009). Fluorescence parameters has also been used for mapping QTL in relation to drought stress in wheat (Czyczyło-Mysza et al 2011), rice (Gu et al 2012) and barley (Guo et al 2008;Wójcik-Jagla et al 2013), salt tolerance in barley (Aminfar et al 2011) and biomass and yield in wheat (Czyczylo-Mysza et al 2013). However, to our knowledge there have been no previous efforts to associate chlorophyll fluorescence with WLT, besides research by Pang et al (2004) and Bertholdsson (2013), who used it to characterise WLT of barley cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…In barley, the identification of QTLs underlying main agronomic traits like GY (Thomas et al, 1998; Liu et al, 2015), malting quality (Borem et al, 1999; Beecher et al, 2001), disease resistance (Chen et al, 1994; Steffenson et al, 1996), drought tolerance (Mohammadi et al, 2005; Peighambari et al, 2005), and salt tolerance (Siahsar and Narouei, 2010; Aminfar et al, 2011) has been reported using molecular markers.…”
Section: Introductionmentioning
confidence: 99%